2018
DOI: 10.1109/tmi.2018.2798801
|View full text |Cite
|
Sign up to set email alerts
|

3-D Reconstruction in Canonical Co-Ordinate Space From Arbitrarily Oriented 2-D Images

Abstract: Limited capture range, and the requirement to provide high quality initialization for optimization-based 2-D/3-D image registration methods, can significantly degrade the performance of 3-D image reconstruction and motion compensation pipelines. Challenging clinical imaging scenarios, which contain significant subject motion, such as fetal in-utero imaging, complicate the 3-D image and volume reconstruction process. In this paper, we present a learning-based image registration method capable of predicting 3-D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 42 publications
0
71
0
Order By: Relevance
“…This is demonstrated on the current state-of-the-art for pose estimation, PoseNet, where we show that our method achieves similar performance as the carefully tuned approximation used in [7]. We also show significant improvements for medical image pose estimation and outperform the state-of-the-art in this domain [4,3]. Acknowledgements: Supported by the Wellcome Trust IEH Award [102431] and Nvidia.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…This is demonstrated on the current state-of-the-art for pose estimation, PoseNet, where we show that our method achieves similar performance as the carefully tuned approximation used in [7]. We also show significant improvements for medical image pose estimation and outperform the state-of-the-art in this domain [4,3]. Acknowledgements: Supported by the Wellcome Trust IEH Award [102431] and Nvidia.…”
Section: Resultsmentioning
confidence: 52%
“…We derive appropriate gradients that are required for CNN back propagation. Our method couples the translation and rotation parameters, and regresses them simultaneously as one parameter on the Lie algebra se (3). We show that our loss function is agnostic to the architecture by training different CNNs and can effectively predict poses that are comparable to state-of-the-art methods.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Deep learning has been successfully applied to image registration [29,30], but in nonlinear image registration tasks with high accuracy requirement, such as brain shift correction, further exploration is still needed [31]. The two submissions that used DL in this challenge were from Sun et al [11], who did not participate to the second phase, and Zhong et al [17] (team FAX), who ranked first in the results reported on the training database.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on slice-to-volume registration in fetal MRI has shown a strong need for regularization and initialization of slice transformations through hierarchical registration [23], [24] or state-space motion modeling [25]. Learning-based methods have been recently used to improve prediction of slice locations in fetal MRI [26], [27] and fetal ultrasound [28]. In [26], [27] anchor-point slice parametrization was used along with the Euclidean loss function based on [29] to predict slice positions and reconstruct fetal MRI in canonical space.…”
Section: Contributionsmentioning
confidence: 99%